Analysis of Zakat Maal Management to Improve the Dhuafa Economy (Case Study on Laznas IZI North Sumatra) - Saidatul Mardiyah; Alfi Amalia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the management of zakat maal in improving the welfare of the poor with a case study on LAZNAS IZI North Sumatra. The research uses a descriptive qualitative method through interviews, observations, and document review. The results show that zakat collection is carried out through several mechanisms, such as direct payments, bank transfers, zakat pick-up services, and socialization to muzaki. However, low zakat literacy is still an obstacle in optimizing the potential for collection. In terms of distribution, zakat is distributed in a consumptive and productive form with a transparent survey and reporting system. This pattern is considered more advanced than a number of other zakat institutions that tend to be consumptive. Empowerment programs such as Lapak Berkah, business capital assistance, skills training, and scholarships have been proven to be able to increase the income and independence of some mustahik. However, the impact is not even due to the limitations of mentoring and low literacy of the beneficiaries' businesses. Other obstacles encountered include the scattered location of mustahik, the minimal number of companions, inappropriate use of funds, and limited program funds. Overall, the management of zakat maal in IZI North Sumatra contributes positively to improving the welfare of the poor, although it needs to be strengthened through continuous mentoring, increasing financial literacy, and wider cooperation so that the results are more optimal and sustainable.